(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This thesis explores the theme of the East in English literature from the 17th to the 20th centuries. The topic is particularly relevant today as the representation and influence of Eastern culture in English literature gain increasing attention in the context of globalization. Through this theme, the thesis analyzes the depictions of the East in literature, stereotypes, and their significance in contemporary contexts.